Phonetic and Lexico-Grammar Influences of the French Language on the English Learning Process in Beninese Secondary Schools - TEBA, Corneille Sourou; SALAMI, Amadou (My University, 2020)
Benin EFL learners face some challenges in the teaching/learning process. One of the most remarkable difficulties in this process is the pronunciation problem. This paper explores the phonetic and lexico-grammar influences of the French language on the English Learning Process in Beninese Secondary Schools. The methodology adopted during the investigation is quantitative and qualitative one. It consists in collecting information from EFL teachers and learners through the means of classroom observation and questionnaires. The data obtained from questionnaires have been analyzed and discussed in order to draw out relevant conclusions. The results obtained reveal that learners are facing challenges in the English language skills such as: listening, speaking, reading and writing. Taking into account what has been said so far, ways and means have been suggested to reduce the negative influences of the French language on Beninese EFL learners.
Keywords: Pronunciation; difficulties; influence; English language; foreign language